(3efXheI aj hajGJ LeGYI ef GdCYdGes - (3GdgdGdj , CHh GdYHGS CMeO Hf YHO GdYRjR Hf GdQTjO GdgdGdj GdSLdeGSj,J (B1175 (3g` s
(3ChdgG (B:s
(3UGQ Edi Gddg GdYXje eGdc HWjHI SfI aGReGdc s
(3BNQgG (B:s
(3hbO CLGH GdeGRQi GdQShd dMeGeI GdebVi ai YGe QShd s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B151 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B436 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B494) s
Keywords: (3GdJGQjNs